Taxonomic and functional diversity of macroinvertebrate community along the elevation gradient and in different seasons in the upper Jinsha River (Qinghai-Tibet Plateau) - Fubin Zhang; Xiaopeng Tang; Pengcheng Lin; Kunyu Shang; Yu Han; Xin Liu; Chunling Wang (Global Ecology and Conservation, 2025)
Comprehensive insights into the elevational gradients, seasonal shifts in biological communities, and their underlying drivers are critical for crafting effective conservation and management plans for these aquatic environments. However, studies on the impact of elevational patterns and seasonal changes on macroinvertebrate diversity in plateau regions remain insufficient. In this study, we investigated the distribution of macroinvertebrate taxonomic and functional diversity along an altitudinal gradient in the upper Jinsha River, southeast of the Qinghai-Tibet Plateau. In the upper Jinsha River basin, 166 taxa of macroinvertebrate were identified, encompassing 3 phyla, 5 classes, and 46 families. The average abundance was 132.5 ± 110.7 ind./m² during the rainy season and significantly increased to 595.3 ± 559.0 ind./m² during the dry season. Generalized linear models (GLM) revealed that the Shannon-Wiener and Simpson indices increased with elevation in both the wet and dry seasons. Conversely, functional richness and Rao's quadratic entropy exhibited a negative correlation with elevation. Redundancy analysis revealed that water temperature, electrical conductivity, pH, and salinity were the predominant environmental parameters shaping the composition of macroinvertebrate communities. Moreover, utilizing the generalized additive model (GAM), we discerned that water temperature and electrical conductivity significantly influence the functional diversity of macroinvertebrates. Our study demonstrated that seasonal variation drives functional diversity via fluctuations in water temperature and conductivity and elevational gradients influence functional diversity through resource constraints. These findings suggest the necessity for conservation strategies that reducing external disturbances in the aquatic habitats of the Qinghai-Tibet Plateau.